Immediate Effect of Baricitinib on Arthritis and Biological Disease-Modifying Antirheumatic Drug-Induced Psoriasis-Like Skin Lesions in Two Patients with Rheumatoid Arthritis - Tada, Yoshifumi; Ono, Nobuyuki; Koarada, Syuichi (Case Reports in Rheumatology, 2021)
Biological disease-modifying antirheumatic drugs (bDMARDs) are very effective for treating rheumatoid arthritis (RA). However, they sometimes induce adverse events such as psoriasis-like skin lesions. We describe psoriasis-like skin lesions that developed simultaneously with an RA flare in patient 1 during treatment with abatacept and in patient 2 soon after starting certolizumab pegol. The skin lesions persisted in patient 2 despite stopping certolizumab. Baricitinib was initiated because of RA flare and resulted in immediate beneficial effects on arthritis as well as skin lesions. The RA went into remission in both patients, and the psoriasis-like skin lesions disappeared within four weeks (patient 1) and three months (patient 2).